Epidemic of hand, foot and mouth disease in West Bengal, India in August, 2007: A multicentric study - Sarma Nilendu; Sarkar Abhijit; Mukherjee Amlan; Ghosh Apurba; Dhar Sandipan; Malakar Rajib (Wolters Kluwer Medknow Publications, 2009)
Background: Hand, foot, and mouth disease (HFMD) is caused mostly by Coxsackievirus A16 (CA16) and enterovirus 71 (EV71). Epidemic of HFMD has occurred in India only once in Kerala in 2003. We report here a recent outbreak of HFMD in three districts of West Bengal, India. Materials and Methods: A case detection system developed with 1) three private clinics in three districts; two at Howrah and one at Hooghly, 2) Pediatrics Department of two medical colleges in Kolkata, 3) 12 practioners of these three districts with 4) a central referral center at Department of Dermatology, NRS Medical College, Kolkata where all cases from this system were confirmed by a single observer. Pediatric Dermatology unit of the Institute of Child Health, Kolkata was another independent unit. Results: A total of 38 cases of HFMD were reported till 08.10.07. Age group ranged from 12 months to 12 years (mean 40.76 months, SD 29.49). Males were slightly higher than females (M:F - 21:17). Disease was distributed mostly over buttocks, knees, hands, feet - both dorsum and palmar or the plantar surface and the oral mucosa. Highest severity noted over the buttocks and the knee. Healing time for skin lesions was 6-13 days (mean 9.13 days, SD 1.93). Oral lesions were found in 33 (86.8%) cases. Conclusion: This outbreak far away from the initial one confirmed regular outsourcing of the virus with possibilities of future epidemics. Also the fact that EV71 induced epidemic is on rise in this part of globe is alarming for India. We hope this early report will be of help for strategic planning for a better management of the disease and prevention of dreaded neurological complications in India.